Pengaruh Work Life Balance dan Job Demands terhadap Work Engagement yang Dimediasi Job Satisfaction: Studi pada Anggota Biro Logistik Polda DIY - Dilla Astuti, Ika; Partina, Anna; Amalia, Bunga Alfausta (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2025)
Human resources are the most crucial element in organizational success. This study aims to analyze the influence of work-life balance and job demands on work engagement, mediated by job satisfaction, among members of the Yogyakarta Regional Police Logistics Bureau. The sampling technique used in this study was the Nonprobability Sampling technique. The method used was the saturated sampling method where the sample in this study were all members of the DIY Regional Police Logistics Bureau totaling 70 people. The data analysis method used was the Hayes Macro Process regression with the help of the IBM SPSS Statistics 26 program. The results showed that work life balance had a negative and insignificant effect on job satisfaction, while job demands had a positive and significant effect on job satisfaction. Furthermore, both work life balance and job demands had a positive and significant effect on work engagement. In addition, job satisfaction also had a positive and significant effect on work engagement. However, job satisfaction did not mediate the effect of work life balance or job demands on work engagement.